Cognitive impairments in autoimmune encephalitis: the role of autoimmune antibodies and oligoclonal bands - Rozenberg, Ayal; Shelly, Shahar; Vaknin-Dembinsky, Adi; Friedman-Korn, Tal; Benoliel-Berman, Tal; Spector, Polina; Yarovinsky, Natalya; Guber, Diana; Gutter Kapon, Lilach; Wexler, Yair; Ganelin-Cohen, Esther (Frontiers in Immunology, 2024)
The presence of oligoclonal bands (OCBs) in cerebrospinal fluid (CSF) is a pivotal diagnostic marker for multiple sclerosis (MS). These bands play a crucial role in the diagnosis and understanding of a wide array of immune diseases. In this study, we explore the relationship between the cognitive profile of autoimmune encephalitis (AIE) and the presence of OCBs in CSF, with a particular emphasis on NMDA receptor antibodies.We studied a cohort of 21 patients across five tertiary centers, segregated into two distinct categories. One group comprised individuals who tested positive only for autoimmune encephalitis antibodies indicative of encephalitis, while the other group included patients whose CSF was positive for both autoimmune encephalitis antibodies and OCBs. Our investigation focused primarily on cognitive functions and behavioral alterations, supplemented by auxiliary diagnostic assessments such as CSF cell count, magnetic resonance imaging (MRI), and electroencephalogram (EEG) results, evaluated for the two patient groups. To validate our findings, we employed statistical analyses such as Fisher's exact test with Benjamini-Hochberg correction.Results: Our study included 21 patients, comprising 14 who were presented with only autoimmune encephalitis antibodies, and 7 who were dual-positive. Among these patients, we focused on those with NMDA receptor antibodies. Of these, five were dual positive, and nine were positive only for NMDA receptor antibodies. The dual-positive NMDA group, with an average age of 27 ± 16.47 years, exhibited significantly higher CSF cell counts (p=0.0487) and more pronounced language and attention deficits (p= 0.0264). MRI and EEG results did not differ significantly between the groups.Our results point to OCBs as an additional marker of disease severity in AIE, especially in NMDA receptor-antibody positive patients, possibly indicating a broader inflammatory process, as reflected in elevated CSF lymphocytes. Regular testing for OCBs in cases of suspected AIE may aid in disease prognosis and identification of patients more prone to language and attention disorders, improving diagnosis and targeting treatment for these cognitive aspects.